The UN Secretariat a brief history (1945-2006) - Thant Myint-U (International Peace Academy, 2007)
The UN Secretariat: A Brief History aims to provide a concise history of the Secretariat as a much-needed background for more informed debate about this under-researched, poorly understood, yet critically important part of the UN system